Ten-Year Monitoring of the Vegetation Composition of the Sisangan Forest Park before and after the Cydalima perspectali Outbreak - Yeganeh Karimi; Esmailzadeh Omid; Azam Sadat Nouraei (بوم‌شناسی جنگل‌های ایران, 2024)
Extended Abstract Background: The Hyrcanus boxwood is the only type of boxwood in the Hyrcanus forests of Iran and one of the few evergreen broadleaf trees in the Hyrcanus forests. Today, boxwood is included in Iran's red list of endangered plants. On the one hand, a major part of the boxwood forests of the Hyrkani region have been destroyed due to the excessive exploitation of boxwood trees during the past decades. On the other hand, the occurrence of the boxwood leaf burn fungal disease and, more importantly, the outbreak of the boxwood moth pest have destroyed large areas of these forests (more than 80-90 percent of them). Due to the importance of the Caspian boxwood and its high value in terms of biodiversity, forest managers are trying to investigate factors affecting this pest in the forest ecosystem. The present study intends to investigate the effect of the boxwood moth pest on the above-below-ground vegetation in the two monitoring periods, namely 2010 and 2022 (before and after the boxwood moth pest outbreak, respectively) in the Buxus hyrcanus Pojark reserve in Sisangan. Methods: The above-ground vegetation was studied with the Braun-Blanquet method at peak vegetation cover by the systematic-selective method in 200 and 400-meter grid dimensions by considering the indicator stand concept in 2010 (and 2022 (before and after the moth pest outbreak, respectively). First, a list of all plant species was recorded in each sample plot by the vegetative form, and then the abundance and predominance of plant species were recorded based on the Brown-Blanke scale. Then, they were accurately identified using the available resources, including Flora Iranica, Persian Flora Collection of Iran, and Color Flora of Iran. The biological form of plants was determined based on the Rankier classification, followed by drawing the biological spectrum. This classification of plants is divided based on the location of regenerating buds where new branches and leaves originate after an unfavorable season. To investigate the geographical distribution or chorology of the plants,  their distribution areas were first determined using the mentioned floral sources, and then the chorotypes of the species were divided based on the classification of geographical areas and toxic floristic areas. The geographical distribution spectrum of plants in the region was also drawn in the form of a histogram. Results: The results showed that 52 and 69 species in 2010 and 2022 were respectively identified in the Sisangan boxtree (B. hyrcanus Pojark) forest reserve. In 2010, Phanerophytes and Cryptophytes with 44% (23 species) and 19% (10 species) were the most present trees, respectively. In 2022, Phanerophytes and Trophytes with 38% (26 species) and 23% (16 species) were the most important biological spectrums, respectively. The results of examining species diversity, evenness, and species richness indices revealed a significant difference (P < 0.001) between the values of species diversity, evenness, and species richness indices in two monitoring periods (2010 and 2022). The indicators of species diversity, uniformity, and species richness of Rosemary cover were significantly different (P < 0.001/001) between the values of Rosemary species diversity, uniformity, and species richness indicators in two monitoring periods (2010 and 2022). In the examination of the degree of similarity between past and present vegetation of the Shamshad Sisangan Reservoir using Jaccard and Sorenson functions, the degree of similarity of Rosemary vegetation was small in the two monitoring periods. The occurrence of any natural disturbance in the forest communities causes a change in the sequence of vegetation and a decrease in the similarity between the vegetation before and after the disturbance. Therefore, the results of this research showed that species richness and diversity increased with the intensity of leaf-eating by the pest of boxwood moth and the opening of the canopy. Because the characteristics of the disturbance regimes strongly affect the dynamics and sequence of the forest, the use of a conservation management strategy can play an important role in reducing its effects. Conclusion: This research demonstrates that species richness and diversity increase with the intensity of defoliation by the boxwood pest and opening the canopy. Additionally, because the aboveground in the infected areas is often covered with pioneer and herbaceous species, management strategies should be prioritized to direct the succession path in this reservoir toward the climax stages.